Sri Lanka : Report on the Observance of Standards and Codes; Fiscal Transparency Module-Update. (IMF Staff Country Reports; Country Report ;, 2005)
This report on Sri Lanka's Observance of Standards and Codes highlights the fiscal transparency module. The 2003 Fiscal Management Act has improved the transparency of government fiscal policy. There has been little progress made in eliminating the quasi-fiscal activities of public corporations. Following the sharp rise in world oil prices, the authorities suspended the petroleum pricing formula that ensured that domestic prices reflect market prices in 2004. Prices are administered with periodic ad hoc adjustments.